Design of power substation in Prionezhsky region - Lukianov, Semen (2017)
In the nearest future the Republic of Karelia is waiting for industry growth, which consequently leads to a growth in the number of electricity consumers. In order to occur a power supply of new consumers in the region and to partially unload existing substations, it was decided to build a power substation designed for voltage levels of 110, 35, 10 kV. The substation is designed to solve the issue of power supply and to give impetus to the growth of industry in the region. This work is focused on the designing process of new substation. The main goals of this thesis are to determine the most suitable structure of substation according to techno-economical point of view and to choose equipment according to the structure of substation.